HUBUNGAN ANTARA KONSUMSI ES TEH MANIS DENGAN RISIKO ANEMIA PADA MAHASISWI DI UNIVERSITAS SETIA BUDI - Stevanus Zulkarnaen Wijaya Wara; Lucia Sincu Gunawan; Kunti Dewi Saraswati (Jurnal Medicare, 2025)
Anemia remains a global health problem, particularly among women of reproductive age. Sweet iced tea, which is widely consumed by young women, contains tannins, sugar, and caffeine that can inhibit iron absorption. This study aimed to determine the relationship between sweet iced tea consumption and the risk of anemia among female students at Setia Budi University, Surakarta. This analytical observational study used a cross-sectional design with 68 respondents selected through purposive sampling. Data were collected using a Food Frequency Questionnaire (FFQ) and blood tests (hemoglobin and erythrocyte indices). Data were analyzed using Fisher’s Exact test. The results showed no significant relationship between sweet iced tea consumption and the risk of anemia (p=0.480). Although tannins can inhibit iron absorption, moderate consumption frequency and the habit of drinking tea after meals may reduce this effect. Balanced nutrition education and healthy drinking habits are still needed to prevent anemia among young women.